Two-phase coding multichannel MAC protocol with MAI mitigation for mobile ad hoc networks - Zhang, Lili (2011)
This letter introduces a novel multichannel medium access control (MAC) protocol for mobile ad hoc networks (MANETs) based on a scalable two-phase coding scheme, which eliminates the hidden terminal problem (HTP) without exchange of neighborhood information. Furthermore, power control is incorporated to mitigate multiple-access interference (MAI). Simulation results show that significant improvement can be achieved by the proposed protocol over IEEE 802.11 DCF.